Gender Dynamics in 20th-Century British Drama: The Female Experience in Kane, Churchill, and Pinter (المجلة الدولية للعلوم التربوية والآداب, 2025)
This article explores the portrayals of female characters in the works of Caryl Churchill, Sarah Kane, and Harold Pinter, examining how these playwrights reflect and challenge socio-political changes in gender roles throughout the 20th century in British drama. Through a comparative analysis, the article highlights common themes such as power, agency, and societal expectations, while also addressing the distinct stylistic approaches each playwright employs. Churchill's narratives emphasize collective female experiences and the complexities of ambition, Kane's works confront trauma and personal identity, and Pinter’s characters navigate intricate power dynamics through silence and subtext. The findings underscore the significance of these representations in understanding broader gender issues in literature and invite further exploration into the roles of female playwrights and post-colonial perspectives in contemporary theatre. Ultimately, this analysis contributes to a richer understanding of the evolving discourse on gender and identity within the landscape of British drama.